Recent Advances in Childhood Asthma - Sudigdo Sastroasmoro (Indonesian Pediatric Society, 1980)
Research in bronchial asthma shows striking advances in the last fifteen years. In recent years, advances in immunology and the introduction of beta adrenergic theory (neuro-humoral theory) lead to a new and comprehensive understanding on the pathogenesis and pathophysiology of asthma. Physiological changes in asthma are particularly concerning the affection of smaller air ways, the goal of the newer methods is to find the most sensitive and reliable method to detect small airway alteration. The current advances in the treatment of asthma are the sympathomimetic amines and the related compounds. The use of steroid, sodium cromoglycate and immunotherapy will be reviewed in this paper.